Association between nonnutritive sucking habits and anterior open bite in the deciduous dentition of Japanese-Brazilians - Sato,Vivianne da Cunha Barbosa (2012)
OBJECTIVE: Assess the association between nonnutritive sucking habits and anterior open bite in the deciduous dentition of Japanese-Brazilian children. METHODS: 410 children of Japanese origin were assessed, 206 boys and 204 girls, between 2 and 6 years of age, in schools in São Paulo State, Brazil. Questionnaires concerning their nonnutritive sucking habits were sent to their legal guardians. Chi-square tests (p<0.05) were applied to assess the association between nonnutritive sucking habits and anterior open bite, and the logistic regression test to obtain the relative risk. RESULTS: The prevalence of sucking habits found in the sample was of 44.6% and for the anterior open bite, 4.4%. There was a statistically significant association between anterior open bite and sucking habits (O.R.=10.77), persistence of sucking habits from 2 to 4 years old (O.R.=22.06), and the persistence of sucking habits from 4 to 6 years old (O.R.=17.31). As for the interruption period of the habit, the group that had interrupted the habit for a period equal or inferior to six months showed an increased prevalence of open bite compared to the group without this habit or in which the habit was interrupted for more than six months. CONCLUSION: Japanese-Brazilian children that had sucking habits have greater chance of acquiring anterior open bite in the deciduous dentition.